Performance measurement of facilities management services in Ghana’s public hospitals - Amos, Daniel; Musa, Zairul Nisham; Au-Yong, Cheong Peng (Taylor & Francis, 2020)
The purpose of this paper is to explore and measure the performance of Facilities Management (FM) services in Ghana’s public hospitals. Given that poor FM practices can significantly hinder the delivery of hospitals’ core services, measuring FM performance is a key step towards ensuring optimal service delivery, and an essential tool for effective implementation of FM strategy. The research employs an exploratory sequential mixed methods approach encompassing interviews in multiple cases at the exploratory stage and questionnaire surveys to confirm performance scales through the use of Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that the quality of FM service delivery, finance, learning and growth, as well as internal business operations indicators, exhibit significant influence on the performance of FM. The research also found that internal business strategic measures should be improved. The developed structural model could assist healthcare managers in determining critical performance dimensions, and also serve as a motivational tool for acknowledging FM’s role in healthcare delivery. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.